Minimally Invasive Plate Osteosynthesis (Mipo): A New Armamentarium in the Treatment of Multifragmentary Fractures of the Tibia and Femur - Das, Chandan Kumar; Biswas, Alok Kanti; Chakraborty, Rivu Raj; Matin, Qausarul; Chowdhury, M Nazrul Islam (Journal of Chittagong Medical College Teachers' Association, 2013)
Minimally invasive plate osteosynthesis (MIPO) in multifragmentary fracture of tibia and femur are technically feasible and advantageous as there is less soft tissue injury and less devascularization of the fracture fragments. This is a study to assess the role of MIPO in the treatment of 30 adult patients multifragmentary tibial and femoral fracture. According to A0 classification 20 patients had 43A type, 4 patients were 42B and 4 patients were 33A and 2 patients was 33B type fracture. All were treated with biological plating techniques using indirect reduction method, with limited operative exposure, with out exposing the fracture site. All cases showed radiological union between 16 to 24 weeks and went to full progressive weight bearing in 20 weeks with full range of ankle and knee movement. No case require any bone grafting. Incidence of complications were very low, with only two of superficial infections that were treated with oral antibiotic therapy and in another case a locking screw broke. JCMCTA 2013; 24 (1):14-18